A New Isoprenylated Aurone from the Flowers of Rosa damascene and Its Cytotoxicities - Wang, Huan; Yang, Juan-Xia; Lou, Jie; Li, Limei; Liu, Gui-You; Hu, Qiu-Fen; Ye, Yan-Qing; Gao, Xue-Mei (Asian Journal of Chemistry, 2014)
A phytochemical investigation of the flowers of Rosa damascena resulted in the isolation of a new isoprenylated aurone (Z)-2-(4-methoxybenzylidene)-7,7-dimethyl-7,8-dihydro-2H-furo[2,3-f]chromene-3,9-dione (1), Its structure was elucidated by spectroscopic methods, including extensive 1D- and 2D- NMR experiments. Compounds 1 was tested for their cytotoxicities against five human tumor cell lines, NB4, A549, SHSY5Y, PC3 and MCF7 and it showed potential cytotoxicity against NB4 and SHSY5Y cell lines with IC50 values of 4.8 and 3.4 μM, respectively.